Arabidopsis thaliana: the vegetable Rosetta Stone - Mei Del Testa, A. (Progress in Nutrition, 2008)
It gives me great pleasure to present Alberto Mei del Testa’s fascinating study of the relationship between hieroglyphics and genetic code. As well as agreeing with the thesis expressed by the author. With the same firm belief I attempt to understand something about the work of a great artist whose genius I admire. I am fascinated and enamoured of his art, but my attempts at a significant interpretation trend toward the illogical and inappropriate, much as the artist often declares his inability to explain in words that which he paints. I wholeheartedly believe, as does the author, that hieroglyphics are without doubt a biological phenomenon, and they therefore must be interpreted as one of an infinite number of possible results of the logic of genetic code, at the same time giving due consideration to the development of both within the confines of the history of evolution and the environment. All that remains for me to say is that hieroglyphics and genetics are both codes which only in the future and with more important contributions such as this present study, will we finally be able to fully understand and learn from.Kary B. Mullis